2014
DOI: 10.1016/j.diii.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between imaging and prognostic factors: Molecular classification of breast cancers

Abstract: The new molecular classification of breast cancers defines cancer sub-groups with a distinct prognosis and response to treatment. Studies on the literature deal with the imaging of each tumour sub-type. The radiologist should be familiar with them in order to adapt the care of an aggressive sub-type. In view of the current knowledge, the following have been significantly more often observed: mammographical spiculated mass with echogenic halo in luminal A sub-type; architectural distortion in luminal B sub-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
12
0
3
Order By: Relevance
“…Previous studies have conducted manual chart reviews to describe the correlation between mammographic findings and biomarkers . In the current study, NLP was used to confirm and validate previously reported correlations.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have conducted manual chart reviews to describe the correlation between mammographic findings and biomarkers . In the current study, NLP was used to confirm and validate previously reported correlations.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have conducted manual chart reviews to describe the correlation between mammographic findings and biomarkers. 22,23,30 In the current study, NLP was used to confirm and validate previously reported correlations. Specifically, we found that patients with the ER 1 subtype were more likely to present with spiculated margins than those with the HER2 1 and TNBC subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Fromtheclinicalpointofview,themostimportant finding obtained in our study is that nodal involvement was observed most frequently in carcinomas withaspiculatedorindistinctmarginonCESM.This might be considered as a confirmation of the results of studies demonstrating that a spiculated margin on radiological examination suggests the presence of asuspectedlesion,whileasharpedge/marginsuggests abenignlesion.Ontheotherhand,ininvasivebreast carcinomasitwasfoundthataspiculatedmargin(on MGorMR)wascharacteristicoflessaggressivemalignancy (of low histological grade, low Ki-67 index [proliferation marker] or luminal A subtype), while asharpmarginwascharacteristicofhighaggressiveness(highhistologicalgradeortriple-negativephenotype) [4,5,7,8].SimilarlytoHuanget al [9](who studieddynamiccontrast-enhancedMRIfeatures),we didnotfindarelationbetweentumourgradeandtumourmarginonCESM.Goingfurtherinourdeliberations,basedonotherauthors'results,itwaspostulated thatthepresenceofaspiculatedtumourmargin(on classical MG or MRI) might reflect two processes of different clinical significance: (1) peripheral invasion ofcancerintobenignstructures,and (2) [9,10].Inouropinion,theclinical role of a spiculated margin on CESM might be definedaftertheanalysisofitsprognosticsignificance (suchanalysisisbeingplannedforthefuture). Recapitulating, because of differences in mechanisms of lesion visualization with MG and CESM, thereisaneedfortheassessmentofthecorrelationbetweenCESMcharacteristics(lesionmargin,thedegree andpatternofenhancement)andhistological/biological/moleculartumourfeatures.Weplantoenlargethe studiedgroupandincludemolecularand/orhistologicalparameters(e.g.vasculardensity [11])inorderto explainthebasisoftheradiologicaltumourpicture.…”
Section: Discussionmentioning
confidence: 99%
“…Regardingnewimagingtechniques,therearetwo majorissuestobeaddressed:theirdiagnosticusefulness, and the relation between parameters assessed using these techniques and well-known diagnostic/ prognostic/predictive markers (histological, clinical, andmolecular).Inotherwords,itispostulatedthat radiologicalimagesmaycarryinformationaboutlesionpathophysiology [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Although significant advancement has been made in medical imaging in optimizing the diagnostic performance and lesion characterization in conventional morphology based modalities, such as mammography and ultrasound (US), even imaging incorporating pathophysiological parameters such as contrast enhanced breast MRI or diffusion weighted imaging are still limited in the ability to guide such treatment choices in breast cancer and in general in making a differential diagnosis of breast cancer [4,5,6,7,8,9,10]. Specifically, certain imaging findings characterize the luminal subtype: for example, on mammograms, architectural distortion and spiculated mass are often seen; and on US, hallmarks of this subtype consist of posterior acoustic shadowing, irregular shape, angular or spiculated margin, and echogenic halo [11,12,13,14]. However, in general in breast cancer, overlap in anatomic imaging findings, and the significant implications in deferring the diagnosis, often require definitive pathological evaluation, which more often than not, will result in benign findings [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%